2017
DOI: 10.1161/jaha.116.004875
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Value of Transthoracic Doppler Echocardiography‐Assessed Coronary Flow Reserve in Patients With Suspected Myocardial Ischemia Undergoing Myocardial Perfusion Scintigraphy

Abstract: BackgroundAdenosine‐assisted transthoracic Doppler‐derived coronary flow reserve (TDE‐CFR) reflects coronary vascular function. The prognostic and incremental value of left anterior descending coronary artery TDE‐CFR above myocardial perfusion scintigraphy in patients with suspected myocardial ischemia has not yet been studied.Methods and ResultsThree hundred seventy‐one patients (mean age, 62.3±8.7 years; 46.8% males) referred to myocardial perfusion scintigraphy attributed to suspected myocardial ischemia we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 32 publications
0
44
0
Order By: Relevance
“…It has been suggested that coronary microvascular dysfunction (CMD) might be important in the pathogenesis of HFpEF 13 . Interestingly, coronary microvascular function can be assessed non‐invasively by measuring coronary flow velocity reserve (CFVR) by Doppler echocardiography 14 . We hypothesized that CKD patients without symptomatic heart disease could have CMD and that this abnormality might contribute to the development of HFpEF.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that coronary microvascular dysfunction (CMD) might be important in the pathogenesis of HFpEF 13 . Interestingly, coronary microvascular function can be assessed non‐invasively by measuring coronary flow velocity reserve (CFVR) by Doppler echocardiography 14 . We hypothesized that CKD patients without symptomatic heart disease could have CMD and that this abnormality might contribute to the development of HFpEF.…”
Section: Introductionmentioning
confidence: 99%
“…CFR is a composite measure of coronary macrovascular and microvascular status. A reduced CFR is associated to a negative prognosis in several groups of patients, including those with diabetes mellitus, arterial hypertension, ischemic cardiomyopathy, normal coronaries, and CAD [ 47 ]. In patients with IHD, CFR is related to angiographic findings and it is a predictor of the extent and severity of CAD [ 48 ].…”
Section: Coronary Flow Reservementioning
confidence: 99%
“…[15][16][17] Coronary flow velocity reserve (CFVR) is the ratio of hyperemic to rest myocardial blood flow, and it can provide a combined physiological measurement of macrovascular and microvascular ischemia. [18][19][20][21][22][23] Reduced CFVR is reported to convey prognostic information on cardiovascular outcomes in different diseases. 18 Transthoracic Doppler echocardiography (TTDE) for assessment of CFVR is a validated, reproducible method to assess CFVR, and it is suggested by the European Society of Cardiology.…”
Section: Introductionmentioning
confidence: 99%
“…18 Transthoracic Doppler echocardiography (TTDE) for assessment of CFVR is a validated, reproducible method to assess CFVR, and it is suggested by the European Society of Cardiology. [18][19][20][21][22][23] Reduced CFVR is reported to convey prognostic information on cardiovascular outcomes in different diseases. 18 C-reactive protein and albumin are inflammatory markers, and they are associated with atherosclerotic disease and CAD.…”
mentioning
confidence: 99%